Investigating the precision of hydrographic data by comparing the differences between multi-beam and single-beam echo-sounders (case study: Bushehr port in the Persian Gulf) - Pasandeh, Nader; Mosavat, Seyed Shahed; Abadpour, Sepideh; Niya, Ali Kourosh; Tajfirooz, Bahman; Zarei, Seyed Mojtaba; Kazemi, Amir Hossein (The International Hydrographic Review, 2025)
This study examines discrepancies between single-beam and multi-beam data at Bushehr Port, where multi-beam data were processed using mathematical models. Single-beam-derived depths from control points were then interpolated onto these surfaces and compared statistically. The analysis revealed an average depth difference of 0.03 m between the sensors, with a standard deviation of 0.08 m at a 98 % confidence interval, and a root mean square error of 0.21 m. The results confirm that multi-beam surveys with the IHO S-44 standard (Edition 6.1.0), achieve Special Order accuracy while reducing field operation time and costs, and providing more extensive seabed coverage.